(M-n+k)(m+7n-7k)=0

Simple and best practice solution for (M-n+k)(m+7n-7k)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (M-n+k)(m+7n-7k)=0 equation:


Simplifying
(M + -1n + k)(m + 7n + -7k) = 0

Reorder the terms:
(M + k + -1n)(m + 7n + -7k) = 0

Reorder the terms:
(M + k + -1n)(-7k + m + 7n) = 0

Multiply (M + k + -1n) * (-7k + m + 7n)
(M(-7k + m + 7n) + k(-7k + m + 7n) + -1n * (-7k + m + 7n)) = 0
((-7k * M + m * M + 7n * M) + k(-7k + m + 7n) + -1n * (-7k + m + 7n)) = 0
((-7kM + mM + 7nM) + k(-7k + m + 7n) + -1n * (-7k + m + 7n)) = 0
(-7kM + mM + 7nM + (-7k * k + m * k + 7n * k) + -1n * (-7k + m + 7n)) = 0

Reorder the terms:
(-7kM + mM + 7nM + (km + 7kn + -7k2) + -1n * (-7k + m + 7n)) = 0
(-7kM + mM + 7nM + (km + 7kn + -7k2) + -1n * (-7k + m + 7n)) = 0
(-7kM + mM + 7nM + km + 7kn + -7k2 + (-7k * -1n + m * -1n + 7n * -1n)) = 0
(-7kM + mM + 7nM + km + 7kn + -7k2 + (7kn + -1mn + -7n2)) = 0

Reorder the terms:
(-7kM + km + 7kn + 7kn + -7k2 + mM + -1mn + 7nM + -7n2) = 0

Combine like terms: 7kn + 7kn = 14kn
(-7kM + km + 14kn + -7k2 + mM + -1mn + 7nM + -7n2) = 0

Solving
-7kM + km + 14kn + -7k2 + mM + -1mn + 7nM + -7n2 = 0

Solving for variable 'k'.

The solution to this equation could not be determined.

See similar equations:

| 4x+2y=160 | | 93.63=4.7p+8.7p-2.6p | | 634=x^2 | | 16/15= | | y+6=55 | | 6+4(s+3t)= | | 99-n=66 | | 28+z=123 | | 1076=x^2 | | 59+y=104 | | y=-10+-8x+2x^2 | | a-47=29 | | 6x+13-3x-7= | | 228=12x | | y=2x^2-8x-10 | | y-16+15=60 | | 36-2=-45 | | 2.8+2.2+x=0 | | 4.7+10m=6.98 | | 10x+15+13x+26x=180 | | 13x+7=39 | | 72/y-6=6 | | C=5x^2-200x+4000 | | 2+5+x=0 | | 3x^2+x=3.75 | | X^2-46x+225=0 | | 400=x^2 | | (x+15)(x+5)(10x-20)=180 | | t/5-4=13 | | 5.9x=-17.11 | | -2*(t-1)=3*(6t-6) | | (x^2+5x-7)(x^2-x+4)-(x+2)(x-3)= |

Equations solver categories